PENGARUH FEMINISME TERHADAP KEPUASAN HUBUNGAN ROMANTIS PADA PASANGAN DEWASA AWAL DI SURABAYA BARAT - Nistriyani, Chulifah; Anggraini, Aprilya Dian Eky; Dato, Maria Avelina; Grahani, Firsty Oktaria (Esa Unggul University, 2024)
Relationship satisfaction is a goal that is always wanted by every partner, because with relationship satisfaction, it can make the continuation of the relationship harmonious and can also affect the strength of the commitment in the romantic relationship. Romantic relationship satisfaction can be influenced by each other's personality. A person's personality develops. in the early adult phase, where they learn emotions, problem solving, responsibility etc. Women who apply feminist values have life values that can affect their personality. The purpose of this study was to find out whether feminism affects romantic relationship satisfaction in early adult couples in West Surabaya. This research is a quantitative study, using the Wilcoxon test, because the data is not normally distributed with the help of SPSS 21. The results show a sig value of 0.000 <0.05, which means that feminism influences romantic relationship satisfaction in early adult couples in West Surabaya.